D-dimer as an indicator of prognosis in SARS-CoV-2 infection: a systematic review. Issue 2 (13th July 2020) - Vidali, Sofia; Morosetti, Daniele; Cossu, Elsa; Luisi, Maria Luisa Eliana; Pancani, Silvia; Semeraro, Vittorio; Consales, Guglielmo
Background: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) stimulates pro-thrombotic changes. This, combined with its tropism for endothelium and lung structures, may explain its association with thrombotic events, reduction of pulmonary gas exchange, acute respiratory distress syndrome (ARDS) and a composite end-point (intensive care unit, invasive ventilation, death). This study aims to highlight the correlation between elevated D-dimer (an indirect thrombosis marker) and the increased rate of poor prognosis-associated conditions, and to introduce D-dimer-labelled anticoagulant administration as a potentially useful tool to prevent complications and positively influence coronavirus disease 2019 (COVID-19) course. Methods: An online database search (PubMed, Google Scholar, Scopus, Web of Science and Cochrane) was performed between 13 March and 10 April 2020. The most relevant keywords were "D-dimer", "SARS-CoV-2", "COVID-19", "thrombosis" and "ARDS". Selection was independently conducted by three reviewers. References and previews of accepted articles were evaluated. Data inclusion/extraction inaccuracy was limited by the work of three reviewers. Selection bias reduction was addressed by thoughtfully designing the search protocol. Quality assessment was performed with the Newcastle–Ottawa Scale. The systematic review protocol was not registered because we anticipated the very limited available evidence on the topic and due to the urgency of the study. Results: 16 studies were evaluated. Good-quality criteria were reached in 13 out of 16 studies. D-dimer was increased and significantly higher in COVID-19 patients compared with healthy controls, in COVID-19 patients with severe disease or a composite end-point compared with non-severe disease, in ARDS compared with non-ARDS patients and in deceased ARDS patients compared with ARDS patients who survived (all p<0.001). COVID-19 patients treated with anticoagulants demonstrated lower mortality compared with those not treated (p=0.017). Conclusions: Correlations exist between COVID-19 infection, severe elevation of D-dimer levels, and increase in the rate of complications and composite end-point. The appropriateness of early and continuous D-dimer monitoring and labelled anticoagulation as management tools for COVID-19 disease deserves accurate investigation, to prevent complications and reduce interventions. SARS-CoV-2 induces thrombotic changes and intense D-dimer elevation, possibly causing gas exchange reduction, ARDS and a composite end-point (ICU, invasive ventilation, death). Monitoring D-dimer and labelled anticoagulants might improve prognosis. https://bit.ly/3fcYqpx